Connecting the dots – III. Nightside cooling and surface friction affect climates of tidally locked terrestrial planets. Issue 2 (30th May 2016) - Carone, L.; Keppens, R.; Decin, L.
Abstract: We investigate how nightside cooling and surface friction affect surface temperatures and large-scale circulation for tidally locked Earth-like planets. For each scenario, we vary the orbital period between P rot = 1 and 100 d and capture changes in climate states. We find drastic changes in climate states for different surface friction scenarios. For very efficient surface friction ( t s, fric = 0.1 d), the simulations for short rotation periods ( P rot ≤ 10 d) show predominantly standing extratropical Rossby waves. These waves lead to climate states with two high-latitude westerly jets and unperturbed meridional direct circulation. In most other scenarios, simulations with short rotation periods exhibit instead dominance by standing tropical Rossby waves. Such climate states have a single equatorial westerly jet, which disrupts direct circulation. Experiments with weak surface friction ( t s, fric = 10–100 d) show decoupling between surface temperatures and circulation, which leads to strong cooling of the nightside. The experiment with t s, fric = 100 d assumes climate states with easterly flow (retrograde rotation) for medium and slow planetary rotations P rot = 12–100 d. We show that an increase of nightside cooling efficiency by one order of magnitude compared to the nominal model leads to a cooling of the nightside surface temperatures by 80–100 K. The dayside surface temperatures only drop by 25 K at the same time. The increase in thermal forcing suppresses the formation of extratropical Rossby waves on small planets ( R P = 1 R Earth ) in the short rotation period regime ( P rot ≤ 10 d).